Analisis Hubungan Tingkat Pendidikan Akhir Terhadap Produktifitas Karyawan Di PT. Gardena Departemen Store Magelang, Jawa Tengah - Mayda Pramesty Riyadi; Hanung Eka Atmaja (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
This research was conducted with the aim of finding out the relationship between final education level and employee productivity in the cashier and sales assistant departments at PT. Gardena Department Store Magelang City. But as time goes by, global business changes are accelerating and business growth is becoming more uncertain. Therefore, currently many companies are looking for talent with better qualifications to support the challenges of change that will occur in the future. The population was all 128 employees, while the sample taken was 74 respondents. The results of the questionnaire have been tested for validity and reliability, and have been tested for classical assumptions in the form of normality assumptions, multicollinearity assumptions and heterolematicity assumptions. The results of this research show that the level of education has a positive and insignificant effect on employee productivity and job training has a positive and significant effect on employee productivity.